Clinical and radiological correlations in patients with gestational trophoblastic disease - Lima,Lana de Lourdes Aguiar (2016)
Abstract Gestational trophoblastic disease is an abnormality of pregnancy that encompasses a group of diseases that differ from each other in their propensity for regression, invasion, metastasis, and recurrence. In the past, it was common for patients with molar pregnancy to present with marked symptoms: copious bleeding; theca lutein cysts; uterus larger than appropriate for gestational age; early preeclampsia; hyperemesis gravidarum; and hyperthyroidism. Currently, with early diagnosis made by ultrasound, most patients are diagnosed while the disease is still in the asymptomatic phase. In cases of progression to trophoblastic neoplasia, staging-typically with Doppler flow studies of the pelvis and chest X-ray, although occasionally with computed tomography or magnetic resonance imaging-is critical to the choice of an appropriate antineoplastic therapy regimen. Because it is an unusual and serious disease that affects women of reproductive age, as well as because its appropriate treatment results in high cure rates, it is crucial that radiologists be familiar with gestational trophoblastic disease, in order to facilitate its early diagnosis and to ensure appropriate follow-up imaging.